Efficacy of Cinnamomum cassia essential oil as a natural preservative and flavoring agent to improve orange juice quality and safety - Boubrik, Fairouz; Boubellouta, Tahar; Benyoucef, Nabil; Bellik, Yuva; Makmuang, Sureerat; Aït-Kaddour, Abderrahmane; Boufahja, Fehmi; Bendif, Hamdi (Italian Journal of Food Science, 2025)
Essential oils (EOs) are promising safe and natural alternatives for pasteurization and synthetic preservation of orange juice. The current research investigates the efficacy of Cinnamomum cassia essential oil (CCEO) as a natural food preservative and flavoring agent in orange juice. We evaluated the physicochemical, microbiological, and sensorial qualities of the juice treated with CCEO over 28 days of storage at 4°C, with measurements taken on every day 7. Results showed that CCEO significantly improved quality indicators by reducing browning reactions and inhibiting pectin methyl esterase activity (p < 0.05). However, potential hydrogen and titratable acidity remained unaffected (p > 0.05). CCEO significantly (p < 0.05) enhanced the microbiological and sensory properties of orange juice by reducing microbial load and enhancing taste, color, flavor, and the overall acceptability parameters. These findings demonstrated the potential of CCEO as a natural food preservative and flavoring agent for orange juice.